Leadership Style and Work Discipline on employee performance - Puspitasari, Tri Widya; Akbar, Mohammad Aldrin; Lina, Ros (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the combined influence of leadership style and work discipline on the performance of State Civil Apparatus at the Office of Cooperatives, Small and Medium Enterprises in Jayapura City. Research Design and Methodology: The research employs a survey method with a quantitative and associative approach. The sample comprises 69 ASNs selected using convenience sampling from a population of 275 ASNs in Jayapura City. Data was collected through Likert-scale questionnaires and direct observations. Instrument validity and reliability were tested using SPSS and classic assumption tests, including normality, multicollinearity, and heteroscedasticity—multiple linear regression analysis. Findings and Discussion: The results indicate that leadership style and work discipline positively and significantly influence ASN performance. Transformational and transactional leadership styles and high work discipline significantly enhance ASN performance. However, contextual differences affect these relationships, underscoring the need for a holistic approach in ASN performance management. Implications: The study has significant implications for public sector management policies and practices. The findings highlight the necessity of a flexible and integrative approach in applying leadership styles and work discipline to improve ASN performance. Future research should explore specific conditions under which these variables most effectively enhance ASN performance.